The role of metastasectomy in advanced renal cell carcinoma. Issue 7 (3rd July 2019) - Apollonio, Giulia; Raimondi, Alessandra; Verzoni, Elena; Claps, Melanie; Sepe, Pierangela; Pagani, Filippo; Ratta, Raffaele; Montorsi, Francesco; De Braud, Filippo Guglielmo Maria; Procopio, Giuseppe
ABSTRACT: Introduction : So far, clinical experiences have proved metastasectomy as the only approach in the setting of metastatic renal cell carcinoma that may achieve the 'no evidence of disease' status, with an associated improvement in survival. Areas covered : This review aims to summarize the body of knowledge on therapeutic approaches to mRCC, with a specific insight on the role of metastasectomy and on which underlying factors could be good predictors to select patients who may benefit from surgery. In detail, we managed to identify as potential selection criteria: the number of lesions and their site, the DFI, patients' performance status and, most of all, the completeness of resection. Expert opinion : The definition of the optimal treatment strategy of mRCC patients is still an unmet clinical need. The decision-making process about treatment strategy should consider specific tumor's and patient's characteristics, as well as the integration of the available therapeutic approaches with the aim to reach the best clinical outcome. We consider multidisciplinary management mandatory in order to tailor the treatment approach according to the patient and disease features. The experience of clinicians may be considered crucial in order to select the best candidates for a multimodal approach.